STRATEGI PROMOSI DESA WISATA TANJUNGJAYA KEK TANJUNG LESUNG MELALUI PLATFORM DIGITAL - Anang Martoyo; Ninuk Wiliani; Hasan Basri (LP2M Universitas Bina Bangsa, 2022)
The COVID-19 pandemic has paralyzed the economy, especially the tourism industry. The government's decision to reopen tourist areas because the spread of the corona has subsided raised the enthusiasm of the tourism village managers. Advances in information technology are utilized by tourism service managers as a medium to communicate superior tourism service products. This study aims to find out how the promotion strategy by utilizing the Digital Platform in increasing the number of visitors in the Tanjungjaya Tourism Village KEK Tanjung Lesung and developing the surrounding area. The research method used is descriptive qualitative with research instruments in the form of primary data derived from observations, interviews from several visitors, and exposure of local officials as well as secondary data from other relevant literacy studies. The data collection technique used triangulation method with inductive analysis referring to positive beliefs, perceptions, certain criteria, and the relationship between variables. Based on the results of observations and analysis of the marketing situation in Tanjungjaya Tourism Village, it can be concluded that the digital platform-based promotion strategy that has been carried out by tourism service managers is 1) Use of the website belonging to the Ministry of Tourism and Creative Economy, the website of the Tourism and Culture Office of Pandeglang Regency, and the website Official CBT Tourism Village Community, 2) Utilization of social media consisting of Facebook, Instagram, and Youtube, 3) Integrated Marketing Communication (IMC) by involving business actors by utilizing marketplaces such as planethotels, traveloka, agoda, en.tiket, and tripadvisor